Pengaruh Pursed Lip Breathing terhadap Fatigue Pasien GGK di Ruang Hemodialisa RSUD Bahteramas - Maman Indrayana; Armayani Armayani; Wa Ode Rahmadania (Health Information : Jurnal Penelitian, 2018)
From interviews with 10 respondents said that the current conditions experienced were tiredness, dizziness, lack of appetite, activities assisting by their families, and they could not work as usual. The aim of this study was to identify the effect of pursed lips breathing on fatigue in patients with chronic renal failure in the hemodialysis room at Bahteramas hospital. This type of research was a quantitative quasi-experimental study with pre-post test without control. The sample consist of 20 respondents collected using purposive sampling technique, and method of data analysis using paired sample t-test. The p value of statistical anaysis was 0.000. There was an effect of pursed lip breathing on chronic renal failure patients with fatigue.